2010
DOI: 10.1103/physrevlett.105.185502
|View full text |Cite
|
Sign up to set email alerts
|

Role of Surface Reconstructions in (111) Silicon Fracture

Abstract: The (111) cleavage in crystalline silicon was investigated by hybrid quantum/classical atomistic simulations showing that its remarkable stability is largely due to asymmetric π-bonded reconstructions of the cleavage surfaces created by the advancing crack front. Further simulations show that the same reconstructions can induce an asymmetric dynamical response to added shear stress components. This explains why [211] upward steps are much more common than [211] downward steps on (111) cleavage surfaces, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Moreover, as brittle cleavage proceeds through thermodynamic energy balance, it is usually argued that the relevant surface energy is the as-cleaved surface energy 17 . For a surface reconstruction to be relevant to determining the energy balance for fracture, it must form instantaneously from the propagating crack tip 34 . The geometry relaxations we performed allow us to exclude barrierless surface reconstructions.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, as brittle cleavage proceeds through thermodynamic energy balance, it is usually argued that the relevant surface energy is the as-cleaved surface energy 17 . For a surface reconstruction to be relevant to determining the energy balance for fracture, it must form instantaneously from the propagating crack tip 34 . The geometry relaxations we performed allow us to exclude barrierless surface reconstructions.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, graphene is not immune to defect. Any defect that deforms the structure of the original honeycomb lattice has a strong impact in the electronic properties of graphene [14][15][16][17][18][19][20][21][22]. For example, lattice deformation of graphene will introduce effective gauge fields and influence the Dirac fermions in graphene like an effective magnetic field [14,15,23].…”
mentioning
confidence: 99%
“…Previous work 16 has revealed that at speeds below about 1,000 ms À 1 , a crack-tip reconstruction consisting of a five-and seven-membered ring related to the p-bonded Pandey 2 Â 1 reconstruction of the (111) surface 28 forms spontaneously. Because of the broken mirror symmetry of the crystal with respect to {111} planes, the five-seven crack tip reconstruction can form on only one of the two fracture surfaces 27 , the lower surface with respect to the axes of Fig. 1, meaning that successive tip reconstruction events can build up to form large-scale surface features via a positive feedback sinking process 16 .…”
Section: Resultsmentioning
confidence: 99%
“…1a). As was done in many previous studies 6,7,[14][15][16][17][18]27 , periodic boundary conditions were used along the crack front direction, a fully threedimensional investigation being, for now, out of reach of DFT-based atomistic simulations. Previous work 16 has revealed that at speeds below about 1,000 ms À 1 , a crack-tip reconstruction consisting of a five-and seven-membered ring related to the p-bonded Pandey 2 Â 1 reconstruction of the (111) surface 28 forms spontaneously.…”
Section: Resultsmentioning
confidence: 99%